IMAGING EVALUATION OF THE IMPACTED TEETH BY USING AN ORTHOPANTOMOGRAPHY IN KURDISTAN REGION –IRAQ - HANA, SALEEM ANDRAWS; SAEED, MAYSALOON SHAMAN (Journal of Duhok University, 2023)
Objective: This study aimed to investigate the frequency and etiology of teeth impaction in OPG images, focusing on the third molars and canines. Methods. This retrospective cross-sectional analytic study was conducted in the Kurdistan Region of Iraq, encompassing the three major cities of Duhok, Erbil, and Sulimanyia. The study included 6374 patients who underwent OPG for impaction assessment, including 2819 (44.23%) males and 3555 (55.77%) females. The angulation of Impacted Mandibular Third Molars (IMTMs) (Winter, 1926) was used to analyze independent variables in this study. Results. Molar impaction was the most common type of impaction, affecting 1498 (87.04%) of the 1721 impacted teeth, with a higher proportion of females (909, 60.68%) than males (589, 39.32%). Class 2 level B (32.58%), class 3 level C (32.15%), and class 2 level A (10.50%) were the most prevalent Pell types and levels for left LM (p-value = 0.0001 for all, p value = 0.2946 for class 3 levels B). Class 2 levels B (30.91%), class 3 Level C (26.20%), and Class 2 Level A (11.78%) for right LM showed a statistically significant difference between male and female patients for the left DM. Conclusion: The most frequent types of impacted LM were the maxillary and canine teeth. These findings contribute to the existing knowledge on the factors that influence impaction and provide insights for the development of effective prevention and treatment strategies